Permanent Education in Health: attributions and deliberations to the light of the National Policy and the Pact of Management - Selma Regina de Andrade; Betina Hörner Schlindwein Meirelles; Gabriela Marcellino de Melo Lanzoni (O Mundo da Saúde, 2011)
This study aimed to analyze comparatively among health managers the structure established in the domain of Education in Health and the evolution of the organization, articulation and implementation of the guidelines of Policy of Permanent Education in Health, from the deliberations of the collegiate organs. A documentary research was done, with application of the case study method, carried through in available document made available by the State manager and official documents of the State Council of Health (Conselho Estadual de Saúde) and the Intermanager Bipartite Commission (Comissão Intergestores Bipartite) of Santa Catarina. The results had emphasized the creation of the Commission of Education- Service Integration (Comissão de Integração Ensino e Serviço), the incentive to qualification of workers with the approval of the Telehealth and Digital Inclusion Projects (Telessaúde e Inclusão Digital) and the offer of Education Courses in the elementary, technical and specialization levels. The panorama in state Santa Catarina shows the increasing consolidation of elaboration and execution actions of permanent education, despite incomplete as regards functioning, considering the regional diversity and the different moments of management of Unified Health System in towns.